PENGUKURAN KINERJA DI SEKTOR PUBLIK - Endang Wirjatmi Trilestari, (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
Government may not be the single agent in delivering public services. The role ofgovernment is diminishing as the society is getting more and more empowered both socially and economically. As Osborne and Geabler stated twelve years ago, the role of government should be steering rather than rowing in order to enable the society to fulfill their own needs. However, equity still grows to be the main concern for both public and private services. For that reason, the role of government is still required to manage equal access to services. Both government and society have become interesting objects of study for public sector performance. In this study, government’s capability is not the only aspect to be analyzed. It also involves the society as the partaker in fulfilling their own needs. Therefore, it is not surprising as Stewart suggests that the services should be oriented for the society and not to the society.